Pengaruh Pendapatan Perkapita dan Economic Growth Terhadap Tax Ratio pada Negara Asia Tahun 2015-2023 - Putri Aulia; Neni Maryani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the effect of per capita income and economic growth on the tax ratio in Asian countries during the 2015–2023 period. The tax ratio is an important indicator used to measure a country's ability to generate tax revenue relative to its Gross Domestic Product (GDP). This research employs a quantitative method with descriptive and associative approaches. Secondary data were obtained from the World Bank, OECD, and Worldometer databases. The sample consists of 27 Asian countries observed over the 2015–2023 period, resulting in 243 observations. Data were analyzed using multiple linear regression preceded by classical assumption tests. The results indicate that per capita income has a positive and significant effect on the tax ratio, with a significance value of 0.025 (<0.05), suggesting that higher income levels can broaden the tax base and increase tax revenue. Meanwhile, economic growth does not have a significant effect on the tax ratio, with a significance value of 0.137 (>0.05), indicating that economic growth is not always accompanied by optimal increases in tax revenue. Simultaneously, per capita income and economic growth significantly affect the tax ratio, with a significance value of 0.041 (<0.05). These findings confirm that improvements in public economic capacity and economic growth collectively contribute to enhancing tax performance in Asian countries.